Penerapan Restorative Justice Sebagai Mekanisme Penyelesaian Kekerasan dalam Rumah Tangga Di Kejaksaan Negeri Bukittinggi - Rahmatsyah, Ricky; Yustrisia, Lola; Munandar, Syaiful (Faculty of Law, Diponegoro University, 2023)
The purpose of this study was to find out the implementation, constraints and efforts to resolve the crime of domestic violence at the Bukittinggi State Prosecutor's Office in accordance with the Bukittinggi Police report letter No.Lp/B/254/X/2022/SPKT/Bukittinggi Police/Polda West Sumatra. The research method used is the empirical juridical method and the type of research that the authors conducted was qualitative research. The primary data in this study was data collection through interviews, where in this data collection the authors conducted question and answer directly to the informants. Secondary data in this research is by collecting data through document studies from both books and journals. In essence, restorative justice is regulated in Law No. 23 of 2004, Attorney General Regulation No. 15 of 2020 and Law No. 11 of 2021. In Attorney General Regulation No. 15 of 2020 it is explained that the conditions for restorative justice to occur are that the suspect has committed a crime for the first time, has an amicable note, criminal acts in prison cannot be more than 5 years, losses incurred are no more than Rp. 2.5 Million. In the research that the authors conducted, the results of this study showed that there were no peaceful efforts from the defendant or the victim, so that the defendant was processed by law with a verdict that the defendant was given a prison sentence of 1 month and 8 days.